The Effect of Learning Media in Guided Inquiry Model Settings on Students' Science Process Skills in Senior High School of Taman Siswa Pematangsiantar - Irwan Lihardo Hulu; Dian Perayanti Sinaga (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2022)
The use of media in the Guided Inquiry Model setting is an active learning process that uses learning media in teams, guided inquiry activities to develop knowledge, questions to improve critical and analytical thinking skills, problem solving, reporting, metacognition, and individual responsibility. This research was conducted with the aim of knowing the effect of the google classroom learning media in the Guided Inquiry model setting on science process skills in ecosystem material in class X SMA Taman Pematangsiantar students in the 2020/2021 academic year. The population in this study were 140 students consisting of 4 classes. Sampling was done randomly, using cluster random sampling. Data analysis was carried out by determining the normality, homogeneity, validity and reliability tests, and the hypothesis was proven by the t-test. at the significant level = 0.05. From the results of hypothesis testing, it is obtained tcount (tcount = 3.56 > ttable 1.66), so H0 is rejected and Ha is accepted, meaning that there is an influence of the Google classroom learning media in the Guided Inquiry model setting on science process skills in ecosystem material in class X SMA Taman Pematangsiantar students Academic Year 2020/2021. The results of the overall answers from respondents regarding the Google Classroom learning media show that the results of the statement strongly agree at 50.52%, the statement agrees at 40%, and the rest of the students choose the other statement option by 7.48%